THE RELATIONSHIP BETWEEN LISTENING STRATEGIES EMPLOYED BY EFL FRESHMAN STUDENTS AND THEIR LISTENING PROFICIENCY - Amanda Fadia Hayya Pradana (International Journal of Research on English Teaching and Applied Linguistics, 2026)
Listening is an active process of receiving, interpreting, and responding to spoken language. This process is supported by listening strategies, which are conscious techniques cognitive, metacognitive, and socio-affective that help learners understand and manage spoken input. The study is to investigate the levels listening strategies use which categorized as low, moderate, and high, and whether these strategies have a significant relationship with their listening proficiency. It is a quantitative correlational design with 45 EFL freshmen students from a University in Surabaya, chosen through simple random sampling. Data were collected using a Listening Strategy Questionnaire and students’ listening scores from the Test of English Proficiency (TEP), then analyzed with descriptive statistics and Spearman’s rho. The results show that most students were high strategy users (71.1%). Socio-affective strategies used most often (M=3.94, high), followed by metacognitive strategies (M=3.89, high), while cognitive strategies were used at a moderate level (M=3.41). However, the correlation between overall strategy use and TEP listening scores was not significant (p=0.719) the p-value is higher than 0.05, and each strategy category also showed that there is no significant with the listening scores. These findings suggest that listening instruction should combine strategy training with stronger language input and regular listening practice.